Fintech and Its Potential Impact on Islamic Banking and Finance Industry: A Case Study of Brunei Darussalam and Malaysia - Ali, Hassnian; Abdullah, Rose; Zaini, Muhd Zaki (Universitas Muhammadiyah Yogyakarta, 2019)
Fintech is growing at an exponential rate which leads to the emergence of innovative business models. Advanced technologies like Blockchain, internet of things (IoTâ€™s), artificial intelligence (AI), and robotics have become mature enough to create disruption in banking and finance industry both conventional and Islamic finance industry. Brunei Darussalam and Malaysia, both, offer wide range of Shari'a compliant services. The main purpose of this study is to investigate the potential impact of Fintech on the Islamic banking and finance industry in Brunei and Malaysia. Accordingly, this research deals with the qualitative method to accomplish and fulfill the research objectives. Content analysis and Semi-structured interview approach were employed throughout the research. The results clearly show that Fintech hasÂ great potential impact on both conventional and Islamic finance industry. This potential impact is in both ways i.e. positive and negative. And, the response and reaction of Islamic finance industry towards the emergence of Fintech and its potential impact seems very slow as compared to their conventional counterparts. This study has indicated important points which include the necessity for the Islamic financial institution to cope with the growth of Fintech.